HIV/AIDS epidemiology, transmission, and risk factors - Blattner, William (Henry Stewart Talks, 2007)
Introduction to scope and impact of the HIV/AIDS global epidemic, Emerging trends in HIV infection reflecting underlying population characteristics, Mechanisms and risk factors for HIV infection, Viral and host factors that impact HIV spread, Emerging insights about treatment as prevention, Framework for ending the HIV epidemic through the 90 90 90 framework, Current challenges to meeting 90 90 90 framework goals
Updated at 2018/11/29